Vāṣiṅṭan̲il tirumaṇam - Cāvi (Kavitā Papḷikēṣan̲, 2012)
Novel on South Indian marriage in Washington; previously serialized in 'Ananda Vikatan', a Tamil weekly
Novel
Keywords: Tamil fiction; Marriage customs and rites; Fiction